2018
DOI: 10.1007/s13224-018-1120-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Foetal Head–Perineum Distance Prior to Induction of Labour as a Predictor of Successful Vaginal Delivery

Abstract: Background In modern obstetrical practice, incidence of induction of labour is on rise for varied maternal and foetal indications. Ultrasound can help obstetricians in counselling patients before induction of labour and explain the probability of successful induction.Objectives To study the role of foetal head-perineum distance in predicting successful vaginal delivery and to correlate with other parameters such as cervical length and Bishop score. Design This study is a prospective case-control study in a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Kim et al found maternal oral fluid therapy to facilitate the transfer of water to the fetus and increase fetal urine production [ 5 ]. Ali et al reported a significant increase in AFI after the intravenous infusion of one liter of fluid in amniorrhexis, although they failed to clarify the etiology of the hydration-associated increase [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al found maternal oral fluid therapy to facilitate the transfer of water to the fetus and increase fetal urine production [ 5 ]. Ali et al reported a significant increase in AFI after the intravenous infusion of one liter of fluid in amniorrhexis, although they failed to clarify the etiology of the hydration-associated increase [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to Bishop's score and cervical length, HPD was more predictable in every way. Saroyo et al, [13] from Indonesia offered a 43.5 cm HPD cut-off with 98 percent sensitivity and 80 percent specificity for predicting vaginal delivery, whereas Ali et al, [12] from Egypt used a 48 mm HPD cutoff. This gap might be explained by the ethnic variety of the inhabitants of the three nations (Egypt, India and Indonesia).…”
Section: Discussionmentioning
confidence: 99%
“…Fetal head perineal angle by TPUS is a reflection of the dynamics of head progression [25,26]. Kalache et al [1] confirmed that "angle of progression" is a simple US parameter using two objective US landmarks: the symphysis pubis and the leading bony edge of the fetal skull avoiding the ischial spines which are used during digital vaginal examination.…”
Section: Discussionmentioning
confidence: 99%